A meta-analysis of the effect of early enteral nutrition versus total parenteral nutrition on patients after pancreaticoduodenectomy. Issue 1 (January 2020) - Cai, Jie; Yang, Gang; Tao, Yun; Han, Yong; Lin, Likai; Wang, Xinghuan
Abstract: Background: An appropriate nutritional support is an important consideration for patients undergoing pancreaticoduodenectomy (PD). Recently, early enteral nutrition (EEN) has been considered to be more effective than total parenteral nutrition (TPN) for the early recovery of patients after many digestive tract surgeries. However, there is little evidence to support EEN in patients undergoing PD. Methods: A systematic literature review was performed to identify relevant studies before December 2018. Statistical analysis was carried out using Review Manager 5.3. Results: Nine studies with 1258 patients were included in the meta-analysis. Six studies compared EEN and TPN and three compared two strategies combined vs. a single strategy. The length of hospital stay (LOS) in the EEN group was significantly shorter than that in the TPN group ( P  < 0.001). There was no difference in the risk of postoperative complications, infections, and mortality between the EEN and TPN groups. In the comparison of two combined strategies vs. one, no significant difference was seen in overall postoperative complications, LOS, or mortality. Conclusion: Compared with TPN, EEN is a safe strategy and can substantially shorten the LOS of patients.